2008
DOI: 10.2753/pin1099-9922100303
|View full text |Cite
|
Sign up to set email alerts
|

The Hierarchy of Ethical Values in Nonprofit Organizations: A Framework for an Ethical, Self-Actualized Organizational Culture

Abstract: Using Maslow's theory of human psychological development as a framework, a model based on the hierarchy of values is proposed to explain how not-for-profit organizations develop an ethical culture. As with individual values, the five levels of ethical behavior-financial competence, accountability, reciprocity, respect, integrity-are attained successively and one at a time. Thus ethical values are a foundation for achieving integrity, defined herein not only as incorruptibility but as a total commitment to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…It is debateable whether not-for-profit organisations genuinely believe that they have a responsibility to create trust by accounting to stakeholders through public discourse (Dhanani andConnolly 2012, Strickland andVaughan 2008), or whether organisations require support of "definitive" stakeholders to gain resources in order to survive (Connolly and Hyndman 2013b). However, both interpretations of these stakeholder models support the notion that good accounting means disclosing information that meets stakeholder need.…”
Section: Charity Accountability Considerationsmentioning
confidence: 99%
“…It is debateable whether not-for-profit organisations genuinely believe that they have a responsibility to create trust by accounting to stakeholders through public discourse (Dhanani andConnolly 2012, Strickland andVaughan 2008), or whether organisations require support of "definitive" stakeholders to gain resources in order to survive (Connolly and Hyndman 2013b). However, both interpretations of these stakeholder models support the notion that good accounting means disclosing information that meets stakeholder need.…”
Section: Charity Accountability Considerationsmentioning
confidence: 99%
“…Here, this type of phenomenon refers to a leadership style that contains a broad common basis together with certain differences that relate to (a mix of) (a) sectoral and cultural characteristics, (b) the extent of publicness, and (c) prevailing organizational challenges (Heres & Lasthuizen, ). In the nonprofit sector, most ethical issues and challenges appear when the sector's core values—namely, financial competence, accountability, reciprocity, respect, and integrity—are endangered (Jeavons, ; Strickland & Vaughan, ). More precisely, nonprofit organizations are continuously seeking a balance between ensuring internal organizational stability on the one hand and being sufficiently accountable, respectful, and open toward the external public on the other hand (BoardSource, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, nonprofit organizations are increasingly asked to be more efficient (Allen, Winston, Tatone, & Crowson, ; Miragaia, Brito, & Ferreira, ). In general, leaders in nonprofit organizations are confronted with strong competition for, and a dependency on, (scarce) external funding (Allen et al, ; Jurkiewicz & Massey Jr, ; Strickland & Vaughan, ). Besides that, they are also dependent on the confidence of the public to enable effective organizational functioning (Jeavons, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrity systems are a form of social capital – they are there to make government work better. Studies have shown that organisational culture is one of the most important factors influencing organisational behaviour, especially with regard to integrity (Strickland and Vaughan 2008). It is therefore important that APS leaders drive cultures consistent with the APS Values and the code.…”
Section: Where To Now?mentioning
confidence: 99%